Swaziland Social Accounting Matrix (SAM), 2007 - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The Swaziland Social Accounting Matrix, 2007 is an update of the 2004 SAM using UN National Accounts data, UN Comtrade data and selected publications from the IMF, World Bank, and OECD/ADB. The SAM provides a detailed representation of the Swaziland economy. It separates 22 activities and 24 commodities; labor is disaggregated by 3 skill groups; and households into 6 groups based on the rural/urban and income status of the household head. The SAM is a useful database for conducting economy-wide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.